2012
DOI: 10.1038/jid.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

α-MSH-Stimulated Tolerogenic Dendritic Cells Induce Functional Regulatory T Cells and Ameliorate Ongoing Skin Inflammation

Abstract: The neuropeptide α-melanocyte-stimulating hormone (α-MSH) is a well-known mediator of skin pigmentation. More recently, it has been shown that α-MSH also exerts a strong anti-inflammatory and immunosuppressive activity. To elucidate the mechanisms underlying α-MSH-induced immunosuppression, we investigated whether α-MSH affects dendritic cell/T cell communication, as especially this interaction has an important role in the regulation of immune responses. Here, we show that α-MSH, by binding to MC-1R, induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…More recently, it has been shown that α-MSH also exerts a strong anti-inflammatory and immunosuppressive activity. Analysis of α-MSH effects on DCs revealed that α-MSH, by binding to MC-1R, induced regDCs, which were capable of expanding CD4 + CD25 + Foxp3 + regulatory T cells in vitro, as well as in vivo [91]. Notably, α-MSH induced regDCs were capable of generating functional Tregs in human blood.…”
Section: Additional Tolerogenic Pathways In Regdcs: Neuropeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that α-MSH also exerts a strong anti-inflammatory and immunosuppressive activity. Analysis of α-MSH effects on DCs revealed that α-MSH, by binding to MC-1R, induced regDCs, which were capable of expanding CD4 + CD25 + Foxp3 + regulatory T cells in vitro, as well as in vivo [91]. Notably, α-MSH induced regDCs were capable of generating functional Tregs in human blood.…”
Section: Additional Tolerogenic Pathways In Regdcs: Neuropeptidesmentioning
confidence: 99%
“…Notably, α-MSH induced regDCs were capable of generating functional Tregs in human blood. Interestingly, human Tregs expanded via α-MSH-stimulated DCs suppressed the proliferation and cytokine secretion of T-helper-17 (Th17) cells [91]. As α-melanocyte-stimulating hormone is a ligand for the melanocortin 1 receptor (MC1R), which expressed on and play a role in malignant cell function through the Wnt/β-catenin pathway [92], its role in formation and action of tumorassociated regDCs should be further investigated.…”
Section: Additional Tolerogenic Pathways In Regdcs: Neuropeptidesmentioning
confidence: 99%
“…The neuropeptide -melanocyte-stimulating hormone (-MSH) is a known mediator of skin pigmentation, but it also acts as potent immunomodulator capable of expanding thymic-derived and peripherally induced Treg, which inhibit the proliferation of psoriatic mouse as well as human Th1 and Th17 cells (14). The biologic effects of -MSH are mediated by binding to one of five G-protein-coupled melanocortin receptors (termed Mc1r-Mc5r) (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Human tDCs can be cultured in vitro from DC precursors using different compounds (7,18). For this purpose, anti-inflammatory cytokines such as and TGF-b (22)(23)(24), vitamin D 3 (Vit D 3 ) (25)(26)(27)(28), neuropeptides, including vasoactive intestinal peptide (17,29,30) and a-melanocyte-stimulating hormone (31), and anti-inflammatory/immunosuppressive drugs such as dexamethasone (Dexa) (28,32,33) and rapamycin (Rapa) (34)(35)(36) are often employed. However, the compound most suitable for clinical application remains undefined from the viewpoint of tolerogenic potential, stability, and capacity for migration toward secondary lymphoid organs, that is, the area where immune responses occur (37)(38)(39).…”
Section: Endritic Cells (Dcs) Are a Heterogeneous Population Ofmentioning
confidence: 99%